Cat Ninja. 4, Welcome to the 'Burbs - Cody, Matthew; Arbona, Alejandro (Epic! originals., 2022)
"Everyone's favorite feline superhero is back for even more hilarious adventures set in the Cat Ninja-verse. Catch up with Cat Ninja, Master Hamster, and the rest of the family as they face...the suburbs! When Dad buys a new house outside the city, the kids are less than excited about new neighbors, backyard barbecues, and quiet, tree-lined streets. And they're not alone--a summer in the suburbs is enough to make Cat Ninja miss the villains of Metro City! Our hero and his family feel like fish out of water when they arrive in Peaceful Valley, but it won't be long before Dad's new neighborhood reveals its scaly, golden underbelly." --